2015
DOI: 10.1371/journal.pone.0119461
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Evolution and Expression of an Insulin-Like Peptide in the Cephalochordate Branchiostoma lanceolatum

Abstract: Insulin is one of the most studied proteins since it is central to the regulation of carbohydrate and fat metabolism in vertebrates and its expression and release are disturbed in diabetes, the most frequent human metabolic disease worldwide. However, the evolution of the function of the insulin protein family is still unclear. In this study, we present a phylogenetic and developmental analysis of the Insulin Like Peptide (ILP) in the cephalochordate amphioxus. We identified an ILP in the European amphioxus Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Ilp Insulin, IGF1, IGF2 (Guo et al, 2009, Holland et al, 1997, Lecroisey et al, 2015 Insulin, IGF1, IGF2 PD/VEGFR Receptor PD/VEGFR PDGFRA, PDGFRB, FLT3, CSF1R, KIT, VEGFR1, VEGFR2, VEGFR3 (Pascual-Anaya et al, 2013) TRK Receptor Trk NTRK1, NTRK2, NTRK3 (Benito-Gutierrez et al, 2005) Ligand NT NGF, BDNF, NT-3, NT-4 all RTKs Others AKT AKT1, AKT2, AKT3 (Bertrand et al, 2009) PDK PDK (Bertrand et al, 2009) PLCγ PLCγ1, PLCγ2 (Bertrand et al, 2009) PKCα/β/γ PKCα, PKCβ, PKCδ (Bertrand et al, 2009) RAF RAF1, ARAF, BRAF (Bertrand et al, 2009) H/K/NRASa HRAS, NRAS, KRAS (Bertrand et al, 2009)…”
Section: Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ilp Insulin, IGF1, IGF2 (Guo et al, 2009, Holland et al, 1997, Lecroisey et al, 2015 Insulin, IGF1, IGF2 PD/VEGFR Receptor PD/VEGFR PDGFRA, PDGFRB, FLT3, CSF1R, KIT, VEGFR1, VEGFR2, VEGFR3 (Pascual-Anaya et al, 2013) TRK Receptor Trk NTRK1, NTRK2, NTRK3 (Benito-Gutierrez et al, 2005) Ligand NT NGF, BDNF, NT-3, NT-4 all RTKs Others AKT AKT1, AKT2, AKT3 (Bertrand et al, 2009) PDK PDK (Bertrand et al, 2009) PLCγ PLCγ1, PLCγ2 (Bertrand et al, 2009) PKCα/β/γ PKCα, PKCβ, PKCδ (Bertrand et al, 2009) RAF RAF1, ARAF, BRAF (Bertrand et al, 2009) H/K/NRASa HRAS, NRAS, KRAS (Bertrand et al, 2009)…”
Section: Ligandsmentioning
confidence: 99%
“…Two genes, coding for Insulin-like peptides (ILP) were described in the genome of B. floridae (Lecroisey et al, 2015) long after the first description of an Ilp gene in B. californiensis (Chan et al, 1990). Both are ohnologues of vertebrate insulin genes IGF1 and IGF2.…”
Section: Insulin Receptormentioning
confidence: 99%
“…1). Previous studies showed that the insulin-relaxin superfamily have a similar modular organisation as their precursor, including an N-terminal signal peptide, A, B and C domains 2,13 . Post-translational modification leads to cleavage of the signal peptide and the C-peptide, resulting in a mature hormone consisting of the A and B chains.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins exhibit a highly structural conservation. They share conserved cysteine residues required for the formation of disulphide bridges which are the hallmark of this superfamily 2 . The insulin-relaxin superfamily has a variety of functions; they can activate both PI3K/AKT and MAPK pathways that are composed of multiple effectors 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation